Management of the Ministry of Religion in Improving Manasik Hajj Guidance in Jambi Province - Abdullah Saman; Abdul Muntholib; Kasyful Anwar Us (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the management of the Head of the Office of the Ministry of Religion in order to improve the guidance of the pilgrimage in Jambi Province.The method used is a qualitative method, using a case study model in three offices of the Ministry of Religion, namely Jambi City, Kab. Tanjung Jabung Timur and Kab. Tebo. Data collection techniques using observation, interviews and documents. The results of the research findings indicate that the management of the Head of Kankemenag Regency / City has been carried out well at the planning stage, thanks to the support of the guidelines set by the Directorate General of PHU. Based on the SWOT analysis, the authors found: (1) strengths in the form of: regulation, the organizational structure of the Ministry of Religion, ASN human resources, the PHU head certified professional mentor, and public interest. (2) weaknesses in the form of: limited facilities and infrastructure, limited number of PHU Section personnel, and not yet optimal internal synergy at the Regency/City Ministry of Religion Offices. (3) Opportunities in the form of: local government support, PAOH budget, collaboration with related social and educational institutions, and certification of professional Hajj rituals supervisors. (4) Challenges/threats in the form of: low level of congregational education, large number of elderly congregants, limited guidance time with lots of materials, continuation of the COVID-19 Pandemic, abolition of the Hajj ritual guidance budget, weak utilization of online media.